2004
DOI: 10.2754/avb200473020235
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition in Diploid and Triploid Populations of Tench (Tinca tinca L.)

Abstract: The aim of the study was to determine the differences in the composition of fatty acids of intramuscular lipids between diploid (2n) and triploid (3n) tench of identical genetic specifications and raised under the same conditions, in relation to sex (F-female vs. M-male) and age (T 3 -36 months vs. T 3+ -42 months). A total of 137 tench (Tinca tinca L.) siblings were analyzed. The control group consisted of 72 diploid tench (39 F and 33 M) and the experimental group of 65 triploid tench (38 F and 27 M). Elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
4
12
1
Order By: Relevance
“…There were no differences in fillet fatty acid profiles, except for stearic acid and DHA between AFD and AFT groups in our study. Similar results were reported for diploid and triploid tench (Tinca tinca L.) (Buchtova, Smutna, Vorlova, Svobodova, & Flajshans, 2004), rainbow trout (Manor, 2009;Picklo, Raatz, Cleveland, & Rexroad, 2013), and masu salmon (Oncorhynchus masou) (Wang, Xu, Bai, Yin, & Jia, 2015). The results indicate that triploid fish have sufficient fatty acid amounts for human consumption.…”
Section: T a B L E 4 Proximate Composition (% Wet Weight) Of All Femasupporting
confidence: 71%
“…There were no differences in fillet fatty acid profiles, except for stearic acid and DHA between AFD and AFT groups in our study. Similar results were reported for diploid and triploid tench (Tinca tinca L.) (Buchtova, Smutna, Vorlova, Svobodova, & Flajshans, 2004), rainbow trout (Manor, 2009;Picklo, Raatz, Cleveland, & Rexroad, 2013), and masu salmon (Oncorhynchus masou) (Wang, Xu, Bai, Yin, & Jia, 2015). The results indicate that triploid fish have sufficient fatty acid amounts for human consumption.…”
Section: T a B L E 4 Proximate Composition (% Wet Weight) Of All Femasupporting
confidence: 71%
“…The study is a part of a comprehensive assessment of diploid and triploid tench reported also in other published papers by Buchtová and Vorlová (2002), Buchtová et al (2003ab) and Buchtová et al (2004).…”
Section: Fish Tench Genome Manipulations Polyploidy Essential Andmentioning
confidence: 77%
“…The external factors are environment, culturing method, and tropic effects. The internal factors include fish species, feeding regime and digestion, life cycle stage, quantitative and qualitative characteristics of lipids-triacyglycerols, phospholipids and their topographical origin-dorsal and ventral part of muscle tissue (Buchtova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%